THE EFFECT OF FEED RATE AND CUTTING SPEED TO SURFACE ROUGHNESS DURING HOLE BORING OF ALUMINUM WITH ANTI-VIBRATION BORING BAR (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
this study is focusing on the experimental investigation of the effects of cutting parameters on surface roughness during hole boring of 8062 aluminums with anti-vibration boring bar on lathe. Several experiments were conducted with different cutting conditions. Based on the results and using “Minitab 19” software, a mathematic model was made to predict the surface quality in connection with different cutting conditions. Finally, an experiment analysis was carried out to verify the analytical results.